Key Attributes Affecting the Rental Value of Green Commercial Office Buildings in Kuala Lumpur, Malaysia - Tommy Kong Kei Hong,; Shamsudin, Zarina; Masfaliza Mohsen,; Abdul Jalil Omar, (Research in Management of Technology and Business, 2021)
Abstract.  In Malaysia commercial office buildings, sustainable buildings encourage people, especially local and multinational companies, to rent and occupy the business's spaces. There is some question raised among industry players on whether there are any differences in terms of the rental value of green and non-green commercial office buildings. Based on a previous study revealed by Halim (2011), green commercial office buildings fetch higher rental value and it varies to location, the property market might have disfigured due to economic factors. Moreover, according to Kim et al. (2017), the study shows that the certification, locational, building characteristics and lease form have strong impacts on the rental value. So, this research aims to compare the difference in rental value of green and non-green commercial office buildings and to identify the key attributes affecting the rental value of green commercial office buildings in Malaysia. This research was conducted in Kuala Lumpur and the quantitative method approach was used in this research. For the first objective, document review was used meanwhile for the second objective survey method was selected with 90 respondent’s involvement. The data will be analyzed by using Microsoft Excel 2013 software and the result shows that green commercial office buildings rental resulted higher than non-green commercial office buildings with the key attributes such as lease form, lease term, gross rent of the building, occupancy rate, competitor, building age, building classification, number of building story, building location and building size. The findings of this study are given benefits to the industry players, stakeholders, as well as for green policymakers.